Restorative Justice as a New Breakthrough to Reduce Recidivism and Promote Reform in the Criminal Law System - Alfies, L. Alfies Sihombing; Yeni Nuraeni; Komarudin Komarudin; Karunia Karunia (JURNAL USM LAW REVIEW, 2025)
This study aims to evaluate the application of restorative justice (RJ) in reducing recidivism in Indonesia, focusing on its effectiveness, implementation challenges, and potential development in the adult criminal justice system. The method used was a qualitative approach with interviews with judges, prosecutors, and mediators at the Bogor District Court as well as case studies of RJ implementation. The results show that although restorative justice (RJ) offers a more rehabilitative solution compared to conventional approaches, its application in Indonesia is still limited by a lack of understanding of legal officers, social resistance, and limited resources. For example, while in New Zealand the recidivism rate of RJ participants is only 17%, in Indonesia, barriers such as lack of mediator training and limited mediation facilities reduce the effectiveness of the program. This study concludes that the implementation of restorative justice (RJ) can reduce recidivism if followed by increased resource capacity, training of legal officers, and community support. The contribution of this research to science is to provide insights into the implementation of RJ in the Indonesian context, as well as suggest measures to overcome the challenges, in order to improve a more rehabilitative criminal justice system.
Keywords: Criminal Justice System; Policy Implementation; Recidivism; Restorative Justice; Social